Efficacy of antiseptics towards some fungi transmitted by the American cooker Periplaneta americana - Majed Kazem Aboud Al Shibli; Huda Khaled Abdul Amir (Al-Qadisiyah Journal of Pure Science, 2018)
In this study,  fungi transmitted by Periplaneta americana were isolated and identify  then the sensivity of this fungi were tested for five of the common disinfectants Formaline, Povidine, Povidon-Iodin, Dettol, Chloroxylenol and Hydrex. The study also included the distribution of isolated fungi by sex, age of insect and collection sites. Where 100 insects were collected, of which 60 males and 40 females were collected from houses, warehouses and sewage networks located in houses and internal sections in the province of Diwaniyah.The fungi percentage were Basidiobolus sp (10.4%) , Candida albican (0.01%)  , Cladosporium(10.4%), (0.7%) Trichophyton, (18.91%) Rhizopus sp, 14.81) sp. , Phenicillium (6.61%) and Rhodotorula sp. The percentage of disinfectant in the fungus varied according to the type and concentration of the disinfectant and the type of fungus. Formalin was the most effective disinfectant, followed by detol and then hydrox, followed by pofidone and pididone. The concentration was 50% Is more efficient than the 25% and 12.5%.